BUILDING CUSTOMER EXPERIENCE AND SATISFACTION DURING THE COVID-19 PANDEMIC: IMPROVING PRODUCT QUALITY AND SERVICE QUALITY - Fadma Sari; Felicia Wong; Deasy Widya Hayu; Elia Ardyan (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
This study analyzes the driving factors for customer experience and satisfaction during the Covid-19 pandemic. This study uses 105 respondents who are customers of Promise Jiwa. The analysis used is PLS-SEM. The results of this study found that service quality and product quality were able to improve customer experience. Other results state that the more customers have a memorable experience, the more they will have an impact on increasing their satisfaction. This study proposes managerial implications, including improving taste quality, using attractive packaging, increasing food and beverage variants, improving the appearance of food and beverages, and innovation in food and beverages